A comparative study of Facebook vs. paper-and-pencil writing to improve L2 writing skills. Issue 8 (16th November 2016) - Dizon, Gilbert
ABSTRACT: Facebook has best leveraged the rapid technological and societal changes over the past decade to grow into the world's largest social-networking site (SNS). However, research of Facebook has lagged behind other Web 2.0 technologies, particularly in regards to investigating its efficacy versus a control group to improve L2 writing. This study, which involved 30 Japanese university English as a foreign language (EFL) students, aims to fill this gap in the literature by examining three areas of L2 writing, namely – writing fluency, lexical richness, and grammatical accuracy – in an experimental group using Facebook ( n = 16) and a control group ( n = 14) using paper-and-pencil. Both groups underwent a 12-week treatment of two in-class focused freewritings a week. Three writing assessments were administered at the start, middle, and end of the treatment to assess its effectiveness. Results from the Mann–Whitney test showed that the experimental group made more significant gains in terms of writing fluency. On the other hand, neither group made significant progress in lexical richness nor grammatical accuracy. These findings strengthen previous research in support of the use of Facebook in L2 classes and highlight the need for additional studies comparing Facebook with other writing mediums.